2022
DOI: 10.1007/s40096-022-00459-z
|View full text |Cite
|
Sign up to set email alerts
|

A new numerical strategy for solving nonlinear singular Emden-Fowler delay differential models with variable order

Abstract: The present study is related to the numerical solutions of new mathematical models based on the variable order Emden-Fowler delay differential equations. The shifted fractional Gegenbauer, $$C_{S,j}^{(\alpha ,\mu )}(t),$$ C S , j ( α , μ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Sahin & Yilmaz (2020) conducted on the influence of students' attitudes towards subjects found that there was a correlation between students' attitudes and their academic achievements. Knowledge about students' attitudes towards subjects is very important because this information can help students, and teachers, and can be used to develop curricula to improve the teaching and learning process (Ahmed & Melad, 2022). A positive attitude provides students with a better understanding of the nature of learning, it also makes students more open to lessons which could increase their expectations in learning, and reduces students' anxiety levels in the learning process (Silvola et al, 2021).…”
Section: A Introductionmentioning
confidence: 99%
“…Sahin & Yilmaz (2020) conducted on the influence of students' attitudes towards subjects found that there was a correlation between students' attitudes and their academic achievements. Knowledge about students' attitudes towards subjects is very important because this information can help students, and teachers, and can be used to develop curricula to improve the teaching and learning process (Ahmed & Melad, 2022). A positive attitude provides students with a better understanding of the nature of learning, it also makes students more open to lessons which could increase their expectations in learning, and reduces students' anxiety levels in the learning process (Silvola et al, 2021).…”
Section: A Introductionmentioning
confidence: 99%
“…Single or multi-term fractional differential equations (FDEs) provided by spaceand/or time-fractional derivatives have attracted a lot of attention due to there efficiency in modelling many real-world phenomena arising in several fields (see [1][2][3][4][5][6]). Finding analytical or exact solutions of FDEs is difficult to obtain, so several numerical methods are proposed for solving different kinds of FDEs based on the finite difference, B-linear spline, second-order Newton interpolations, spectral method and Bernstein polynomials (see [7][8][9][10][11]). The distributed-order FDEs are a generalisation of the aforementioned two classes of FDEs, in which the fractional derivative order is integrated within a specified range.…”
Section: Introductionmentioning
confidence: 99%
“… The SFGPs' OM techniques have been proven effectiveness in solving many problems. Ahmed and Melad [8] derived a new SFGOM of differentiation and integration in conjunction with the spectral collocation method to solve VO pantograph-delay differential equations and VO pantograph Volterra delay integrodifferential equations, El-Gindy et al, [19] used different kinds of SFGOMs of the VO differentiation and integration to solve the VO Fredholm-Volterra integro-differential equations, systems of VO-FV-IDEs and VO Volterra partial integro-differential equations, Ahmed and Melad [9] extracted a novel numerical strategy that depends on SFGPs to solve nonlinear singular Emden-Fowler VO-DMs, EL-Kalaawy et al [18] proposed SFGOM of integration to numerically find the solution of fractional variation problems and fractional optimal control problems.…”
Section: Introductionmentioning
confidence: 99%